Hypnagogic Frontal EEG Bursts in Children: Epileptic or Not?. Issue 6 (November 2021) - Datta, Anita N.
Abstract : Purpose: Various EEG patterns emerge in drowsiness. Intermittent bilateral midfrontal slowing (BFS) and hypnogogic frontal predominant sharply contoured waveforms (HFSC), maximal at (Fz, F3-4, and Fp1-2), are often encountered. These do not meet the criteria for epileptiform discharges. The study objective was to determine the clinical significance of BFS and HFSC. Methods: Clinical information of children with BFS ( n = 49) and HFSC ( n = 99) was compared with control subjects with generalized spike-wave (GSW) discharges ( n = 102) and normal EEGs ( n = 100). Results: HFSC was present in younger children (mean age was 3.5 ± 3.6 years), whereas BFS was present in older children (mean 12.9 ± 4.8 years). Seizures occurred in the normal EEG, BFS, HFSC, and GSW groups, respectively, as follows: 22 (22%), 15 (31%), 42 (43%), and 100 (98%) patients, whereas epilepsy occurred in 17 (17%), 10 (20%), 35 (35%), and 95 (93%) patients. The GSW group had more seizures and epilepsy than the other groups ( P < 0.001), but the HFSC group also had more seizures ( P < 0.001) and epilepsy ( P < 0.003) than the normal EEG group. Seizures and neurodevelopmental and psychiatric comorbidities were similar between the BFS and normal EEG groups. Notably, the HFSC group had more developmental delay than the normal EEG group [33 (33%) versus 18 (18%), P < 0.009] but were similar to the GSW group 22 (22%). Conclusions: Bilateral midfrontal slowing and HFSC have had unclear significance. Our results suggest that HFSC may be a marker of increased risk of seizure, epilepsy, and developmental delay as compared to children with normal EEGs and has similar risk of developmental delay to those with GSW.